Goltz syndrome with absence of fifth metacarpal and distal phalanx, severe abdominal dehiscence and bladder exstrophy - Bharati Sahu; Smita Rani Samal; Prasenjeet Mohanty; Manas Ranjan Puhan (Wolters Kluwer Medknow Publications, 2016)
Goltz syndrome, also known as focal dermal hypoplasia, is a rare genodermatosis. It is an X-linked dominant disorder characterized by mesoectodermal dysplasia present with cutaneous, ocular, dental, and skeletal defects. Its hallmark is thinning of the dermis resulting subcutaneous fat herniation. We report a case of a 7-month-old female child with typical clinical features of Goltz syndrome with some unusual findings such as severe abdominal dehiscence, bladder exstrophy, and absence of the fifth metacarpal and distal phalanx.